Direct measurement of multi-elements in high matrix samples with a flow injection ICP-MS: application to the extended Emiliania huxleyi Redfield ratio - Zhang, Q; Snow, J; Holdship, P; Price, D; Watson, P; Rickaby, R (Royal Society of Chemistry, 2018)
The quotas of a limited number of trace elements in the extended Redfield ratios have been determined before and thought to reflect the requirements of phytoplankton. However, these quotas are found to be quite variable under different environmental conditions, suggesting that the cellular trace metal quota is not an accurate measure of cellular trace metal requirement. Here we present a method that has been developed and optimised for direct analysis of 32 elements simultaneously in small volume of cell lysate in buffers with a high salt matrix (800 μL, up to 30% TDS). We then demonstrate the application of the method to resolve the extended Redfield ratio of cell requirement by measuring the intracellular trace element composition of six Emiliania huxleyi strains isolated from different locations. The method uses a quadrupole-ICP-MS with a collision/reaction cell to resolve polyatomic interferences. The ICP-MS is interfaced with an Elemental Scientific Flow Injection Automation System (FIAS). The accuracy of the analysis according to this new method is verified by measuring 2 certified reference materials, BCR 273 and BCR 414. This work presents a number of running parameters, optimised for multi-element analysis of samples with a high TDS sample matrix. This method allows direct measurement of protein samples in their native state: no alteration or digestion is needed, which simplifies the steps for sample preparation. In this study with 6 E. huxleyi strains isolated from the environment, our method reveals significant differences between whole cell and intracellular metal quotas for all strains. The intracellular metal composition, interpreted as a truer representation of organisms' metal requirements, shows an environmentally dependent signal. This suggests that, compared with whole cell metal quotas, the metalloproteins are a better indicator of metal requirements of phytoplankton under various environmental conditions.